Stroke - diagnosis and treatment methods - Ręba, Patrycja (Journal of Education, Health and Sport, 2020)
Introduction Stroke is a very serious health problem. Its typical consequences include chronic physical and mental disability, more than half of all patients who survived stroke are dependent, depending on the help of other people even in everyday activities. Stroke is the death of parts of this organ as a result of stopping the blood supply to the brain tissue. There are two main types of stroke: ischemic and hemorrhagic. Aim The aim of the study is to analyze treatment methods and diagnose stroke. Material and method Review of available literature on the subject. Results Ischemic stroke (about 4/5 of stroke cases) occurs when an artery supplying some part of the brain with blood becomes obstructed, i.e. blood does not flow through it or it flows from insufficient amount so that brain cells receive as much as they need. Atherosclerosis is the most common cause of narrowing or blockage of the artery. Hemorrhagic stroke (about 1/5 of stroke cases) occurs as a result of a cerebral artery wall rupture and blood spilling out of the vessel, as a result of which the blood does not reach the brain tissue in the area supplied by the ruptured artery. The blood escaping from the damaged vessel destroys the surrounding nervous tissue and causes an increase in pressure inside the skull, which disrupts the functioning of the entire brain. Hemorrhagic strokes are divided into intracerebral hemorrhages andsubarachnoid hemorrhage. According to the World Health Organization, around 15 million cases of stroke are diagnosed worldwide each year. Of this group, approximately 5 million die and another 5 million suffer from permanent disability. Conclusions Anyone suspected of having a stroke should be taken to hospital immediately and under specialist medical care. Stroke is a medical emergency and the chances of recovery are greater the sooner treatment is started. Stroke, as the most important cause of chronic disability, is a disease that heavily burden the budget of healthcare systems.